Bio-adhesives from soy protein concentrate and montmorillonite: Rheological and thermal behaviour - Bacigalupe, Alejandro (2017)
The incorporation of different amounts of montmorillonite (MMT) to soy protein concentrate (SPC) was used to improve the performance of the bio-nano-adhesive obtained. X-Ray diffraction, rheology, thermogravimetric analysis and scanning electronic microscopy were carried out to characterize the adhesives, and dry and wet strength was used to determine the adhesion strength. In the rheological measurement, the incorporation of up to 3 wt% of MMT did not modify the consistency index values of the SPC, while an increase in the flow consistency index for higher concentrations can be observed due to a strong interaction between MMT and the protein. Besides, the flow point values increase four times with respect to the value obtained for SPC alone. The decomposition temperature of SPC increases with the addition of MMT, which provides a tortuous pathway that obstructs the diffusion of volatile products out of the bio-nano-adhesive. Further addition beyond 5 wt% led to the formation of agglomerates, as verified by SEM. Moreover, the roughness of the fractured surface of the matrix can explain the decrease of the net adhesion of the nano-particles to the SPC suspensions.